Об одной теореме М.А. Красносельского - Ляшко, С.И.; Семенов, В.В. (Кибернетика и системный анализ, 2010)
Доведено критерій розв’язності операторного рівняння другого роду з правильним ендоморфізмом хаусдорфова бочкового простору. Отримане твердження — узагальнення теореми Красносельського про збіжність методу простої ітерації розв’язання рівняння з нерозтягуючим самоспряженим оператором. The solvability criterion for a second-kind operator equation with correct endomorphism of Hausdorff barreled spaces is proved. The resultant assertion is a generalization of M.A. Krasnoselski’s theorem on the convergence of the Picard iteration method for solving equations with nonexpansive selfadjoint operators.